Theology, political theory, and pluralism beyond tolerance and difference - Johnson, Kristen Deede (Cambridge, UK ; New York : Cambridge University Press, 2007)
Tolerance has been the bedrock of political liberalism, while proponents of agonistic political and radical democracy have sought an answer that allows a deeper celebration of difference. Kristen Deede Johnson describes the move from tolerance to difference and the accompanying move from epistemology to ontology, within recent political theory. Building on this "ontological turn," in search of a theological answer to the question, she puts Augustine into conversation with recent political theorists and theologians. This theological option enables the Church to envision a way to engage with contemporary political society without losing its own embodied story and practices.
1. Introduction -- 2. The recent journey of liberal tolerance -- 3. Beyond tolerance to difference -- 4. Augustine and the theological turn -- 5. Towards a theology of public conversation -- 6. Conclusion.
Includes bibliographical references (p. 261-272) and index.
Description based on print version record.
Keywords: Political theology; Cultural pluralism; Theologie; Politische Theorie; Pluralismus; Theologie; Plurale samenleving; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books